A long obedience in the same direction eaudiobook Discipleship in an instant society. - Peterson, Eugene (Hovel Audio, 2006)
As a society, we are no less obsessed with the immediate than when Eugene Peterson first wrote this Christian classic. If anything, email and the Internet may have intensified our quest for the quick fix. But Peterson's time-tested prescription for discipleship remains the same: “ A Long Obedience in the Same Direction.” Tucked away in the Hebrew Psalter, Peterson discovered "an old dog-eared songbook," the Songs of Ascents that were sung by pilgrims on their way up to worship in Jerusalem. In these songs (Psalms 120-134) Peterson finds encouragement for modern pilgrims as we learn to grow in worship, service, joy, work, happiness, humility, community and blessing.